The ICAD (iterative cavity-enhanced DOAS) method - Horbanski, Martin; Pöhler, Denis; Lampel, Johannes; Platt, Ulrich (Atmospheric measurement techniques, 2019)
Abstract. Cavity-enhanced differential optical absorption spectroscopy (CE-DOAS or BB-CEAS DOAS) allows us to make in situ measurements while maintaining the kilometre-long light paths required by DOAS. This technique has been successfully used for several years to measure in situ atmospheric trace gases. A property of optical cavities is that in the presence of strong absorbers or scatterers the light path is reduced, in contrast to classical long-path DOAS measurements where the light path is fixed. Typical CE-DOAS or BB-CEAS evaluation schemes correct this effect using the measured total light intensity attenuation. This makes them sensitive to any variations in the light intensity not arising from the trace gas absorption. That means an important DOAS advantage, to be independent of total light intensity, is actually lost. In order to cope with this problem, the instrument setup would require a thorough stabilisation of the light source and a very rigid mechanical setup, which would make instrumentation more complex and error prone. We present a new approach to cavity-enhanced (CE) DOAS based on an iterative algorithm (ICAD) which actually models the light path reduction from the derived absorbers in the optical resonator. It allows a sensitive and robust data analysis that does not depend on the total light intensity, allowing a simpler and more compact instrument setup. The algorithm is discussed and simulated measurements demonstrate its sensitivity and robustness. Furthermore, a new ICAD NO2 instrument is presented. It takes advantage of the advanced data evaluation to build a compact (50 cm cavity) and lightweight instrument (<10 kg) with low power consumption (25 W) for sensitive measurements of NO2 with a detection limit of 0.02 ppbv at an averaging time of 7 min. The instrument is characterised with a NO2 calibration source and good long-term stability is demonstrated in a comparison with a commercial chemiluminescence detector. As a new application of ICAD we show measurements on an automobile platform to investigate the two-dimensional NO2 distribution in an urban area. The instrument is so robust that even strong vibrations do not lead to any measurement problems.
Gesehen am 02.08.2019